Clinical application of prophylactic internal iliac artery balloon occlusion combined with uterine artery embolization in patients with abnormally invasive placenta. (17th December 2018) - Mei, Youwen; Luo, Dan; Lin, Yonghong
Abstract: Background: The purpose of this study is to investigate the role of prophylactic internal iliac artery balloon occlusion combined with uterine artery embolization (UAE) in patients with abnormally invasive placenta. Methods: Forty cases with abnormally invasive placenta who visited our hospital were analyzed retrospectively from May 2014 to September 2015. Twenty cases who had prophylactic balloon occlusion of internal iliac artery with/without UAE were in the study group, while the other 20 cases in the control group. Volume of estimated blood loss and blood transfusion, rate of hysterectomy, surgery duration, postoperative complication and length of hospitalization were compared between two groups. Results: The mean estimated blood loss in the study group (800 ml, 500–1800 ml) was less than that in the control group (1875 ml, 500–7600 ml) ( p  = .01). Only two cases had blood transfusion in the study group, while 12 cases in the control group. No case was performed hysterectomy in the study group, while one case had the operation in the control group. There was no significant difference in surgery duration, postoperative complications and length of hospitalization between two groups. Conclusion: Prophylactic balloon occlusion of internal iliac artery combined with UAE is effective and safe for patients with abnormally invasive placenta.